2015
DOI: 10.1155/2015/142979
|View full text |Cite
|
Sign up to set email alerts
|

Ginger and Its Constituents: Role in Prevention and Treatment of Gastrointestinal Cancer

Abstract: Gastrointestinal (GI) cancer, a cancer of different organs of the digestive system, is one of the most common cancers around the world. The incidence and death rate of some of these cancers are very high. Although a large variety of chemotherapeutic agents have been introduced since the last few decades to combat GI cancer, most of them are very expensive and have side effects. Therefore, the compounds derived from natural sources, which are considered to be safe and cost effective, are needed. Ginger (Zingibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
255
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(274 citation statements)
references
References 65 publications
6
255
2
11
Order By: Relevance
“…We also showed that GDNPs 2 contains 125 miRNAs (15–27 nucleotides in length) that were unique to GDNPs 2 compared with those reported in grape nanoparticles -all but one of which have the potential to regulate the expression of human genes by binding to their 3′-UTRs. Both 6-gingerol and 6-shogaol, two major anti-inflammatory and anti-cancer compounds, are components of ginger [6466]. Interestingly, we found that GDNPs 2 contained higher concentrations of these active ginger constituents compared with GDNPs 1 and GDNPs 3.…”
Section: Discussionmentioning
confidence: 78%
“…We also showed that GDNPs 2 contains 125 miRNAs (15–27 nucleotides in length) that were unique to GDNPs 2 compared with those reported in grape nanoparticles -all but one of which have the potential to regulate the expression of human genes by binding to their 3′-UTRs. Both 6-gingerol and 6-shogaol, two major anti-inflammatory and anti-cancer compounds, are components of ginger [6466]. Interestingly, we found that GDNPs 2 contained higher concentrations of these active ginger constituents compared with GDNPs 1 and GDNPs 3.…”
Section: Discussionmentioning
confidence: 78%
“…Ginger has an active components such as curcumin [5], 6-gingerol, 6-shogaol and 6-paradol [6,7]. The mixture of honey and ginger has a high antimicrobial activity against Gram-positive bacteria and Gram-negative bacteria [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used around the world in foods as a spice and flavoring agent 57 . It is native to tropical Australia, Asia, Brazil, China, India, West Africa, Jamaica and United States…”
Section: Shunthi (Zingiber Officinale Roscoe)mentioning
confidence: 99%